PROGRAM LAYANAN BELAJAR KEAGAMAAN DALAM MENINGKATKAN SPIRITUALITAS ANAK SEJAK DINI - Hafidz, Nur; Praptia Barkah, Affitri (Balai Diklat Keagamaan Jakarta, 2024)
Abstract Every child is born with the potential for goodness, namely the growth of a sense of self-potential, primary and secondary needs to be able to recognize, and awareness of the existence of God Almighty in him. The communication skills that are built will become a daily habit. Moreover, with a religious learning service program that improves children's spirituality from an early age. There is one Putra Harapan Kindergarten institution that implements a religious learning service program in improving the spirituality of early childhood. This religious learning service program is to make parents aware of the importance of spiritual intelligence being realized. From here it is important to research the religious learning service program in improving children's spirituality from an early age. The goal is, the religious learning service program in improving children's spirituality from an early age can recognize Islam (faith, Islam, and ikhsan) in every aspect of spiritual development in the Harapan Putra Kindergarten school room. This research method uses descriptive qualitative by taking seven samples of children, teachers, and principals at Putra Harapan Kindergarten aged 4-6 years and obtaining the impact of the religious learning service program. Data collection techniques use observation, interviews, and documentation with an active participation model. The results of the study indicate that the religious learning service program in improving children's spirituality from an early age through: (1) Religious Learning Services for Individuals; (2) Religious Learning Services for Groups; (3) Spiritual Implications for Children from an Early Age. These three points are where children will experience changes in their spiritual attitudes and reason which will be evident in their daily religious learning. Abstrak Setiap anak lahir mempunyai potensi kebaikan, yakni tumbuh rasa potensi diri, kebutuhan primer dan sekunder dapat mengenal, dan kesadaran adanya Tuhan yang maha Esa dalam dirinya. Kemampuan komunikasi yang dibangun akan menjadi kebiasaan setiap harinya. Terlebih dengan program layanan belajar keagamaan yang meningkatkan spiritual anak sejak dini. Ada salah satu lembaga TK Putra Harapan yang menerapkan program layanan belajar keagamaan dalam meningkatkan spiritual anak usia dini. Program layanan belajar keagamaan ini untuk menyadarkan orang tua pentingnya kecerdasan spiritual diwujudkan. Dari sinilah penting untuk meneliti program layanan belajar keagamaan dalam meningkatkan spiritual anak sejak dini. Tujuannya, program layanan belajar keagamaan dalam meningkatkan spiritual anak sejak dini dapat mengenal keislaman (iman, islam, dan ikhsan) dalam setiap aspek perkembangan spiritual di ruang sekolah TK Harapan Putra. Metode penelitian ini menggunakan kualitatif deskriptif dengan mengambil tujuh sampel anak, guru, dan kepala sekolah di TK Putra Harapan yang berusia 4-6 tahun dan memperoleh dampak dari program layanan belajar keagamaan. Teknik pengumpulan data menggunakan observasi, wawancara, dan dokumentasi dengan model partisipasi aktif. Hasil penelitiannya menunjukkan bahwa program layanan belajar keagamaan dalam meningkatkan spiritualis anak sejak dini melalui: (1) Layanan Belajar Keagamaan untuk Individu; (2) Layanan Belajar Keagamaan untuk Kelompok; (3) Implikasi Spiritual Anak Sejak Dini. Tiga poin inilah, anak akan memperoleh perubahan dalam sikap dan akal spiritual yang akan melekat dengan dibuktikan keseharian selama belajar keagamaan.